Practices of Care in Storytelling - Alvis, Cole; Bonnell, Yolanda (Percées)

(untitled) (Société québécoise d'études théâtrales (SQET), 2023)
This article features reflections on the recent creation of White Girls in Moccasins by Yolanda Bonnell, coproduced by manidoons collective and Buddies in Bad Times Theatre in the spring of 2022. In preparation for the coproduction, members of manidoons collective gathered a group of production artists to discuss alternative ways of working within theatre; particularly the often-stressful process of tech week that precedes opening night. Also featured is an original poem called “Pow Wow” by Yolanda Bonnell, woven into proposals for keeping each other safe(r) when working in the performing arts.